Functional and motor fitness of 7-8 form pupils as factor of health improvement - Ivashchenko, Olga; Kuznetsova, Olena; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Ivashchenko Olga, Kuznetsova Olena, Zukow Walery. Functional and motor fitness of 7-8 form pupils as factor of health improvement. Journal of Education, Health and Sport. 2016;6(11):325-328. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167512 http://ojs.ukw.edu.pl/index.php/johs/article/view/4004 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 19.11.2016. Functional and motor fitness of 7-8 form pupils as factor of health improvement Ivashchenko Olga1, Kuznetsova Olena2, Zukow Walery3 1H.S. Skovoroda Kharkiv National Pedagogical University, UKRAINE 2Yaroslav Mudryi National Law University, UKRAINE 3Kazimierz Wielki University in Bydgoszcz, POLAND Abstract Purpose: to determine special gender aspects of 7-8 form pupils’ functional and motor fitness. Material: in the research participated boys: 7th form (n=24); 8th form (n=35); girls: 7th form (n=31); 8th form (n=14). Results: analysis shows that between 7th form boys and girls there are statistically confident differences in functional tests (p<0.001). By functional state of respiration and blood circulation functions 7th form boys and girls were assessed as healthy but not trained; by Serkin’s test they had latent circulatory inefficiency. Statistically confident differences between 8th form boys were registered in tests 3-8, which characterized power, speed-power and coordination fitness (р<0.001). By results of other motor tests differences between mean values were statistically unconfident (p>0.05). Conclusions: gender aspects of seven form pupils’ motor fitness are power abilities and ability to assess power parameters of movements; in eighth form they were ability to perceive motor power parameters and static strength. Key words: boys, girls, functional fitness, coordination fitness, power fitness, motor abilities.